SISTEM INFORMASI PENJUALAN GADGET BERBASIS WEB PADA TOKO MITRA ABADI - Artika Surniandari (Paradigma, 2014)
The current website is one tool that is widely used for the delivery of information . The development of the website more and more rapidly . The technology is widely used for medium websites selling as well as promotion of various products , including gadgets . A company need once the existence of an information system support and providing outstanding service to customers . That is one of the reason the author tries to make a draft of the sales system in Toko.Mitra Abadi that until now has not been computerized . At this time Mitra Abadi Stores companies engaged in the sale and service . Sales of existing systems in Stores Mitra Abadi is still done manually , example by following the exhibition and sale in stores , customers who buy goods , to date, only the stopped and happened to see it, maybe there are still many customers who still lack of information or due to busyness can not see the products offered in the store Mitra Abadi gadget sales . Therefore the computerized system is better than manual systems to run more effectively and efficiently , and the system is now more conducive sales compared with the previous system